2018
DOI: 10.31590/ejosat.450363
|View full text |Cite
|
Sign up to set email alerts
|

Sıcaklık ve Farklı Kıvam Verici Maddelerin Ketçabın Reolojik Özellikleri Üzerine Etkileri

Abstract: Bu araştırmada, ketçap formülasyonuna üç farklı (guar gam, ksantan gam ve modifiye mısır nişastası) hidrokolloid ayrı ayrı ilave edilerek laboratuvar ortamında ketçap üretimi yapılmıştır. Hidrokolloid eklenerek üretilen ketçap numunelerinin reolojik davranışları, Anton Paar MCR 302 marka/model reometre cihazı kullanılarak 1-100 s-1 kayma hızı aralıklarında ve geniş bir sıcaklık aralığında (10-50 °C) incelenmiştir. Elde edilen sonuçlar, reometre cihazının yazılım programı (RheoCompass 1.21) kullanılarak Power L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(3 reference statements)
0
0
0
Order By: Relevance
“…Similar studies have revealed that in rheological tests of hydrocolloidal and suspended foods, such food samples can be preferred to slide using smooth geometry (Buscall, 2010). In the rheological analysis of various food suspensions and dispersions such as chickpea puree (tomato puree, quince puree, ketchup, chickpea flour paste) to prevent wall slipping; pre-treatments such as using geometries with rough surfaces (Valencia et al, 2003), homogenizing particle size, using guar gum, xanthan gum and emulsifier additives (Bildir et al, 2018) were applied. After interpreting the shear rate versus shear stress graph by drawing, oscillation tests were also performed on chickpea purees prepared with the same dry matter content using dried chickpea puree powders, and the viscoelastic properties of the purees were determined.…”
Section: Rheological Propertiesmentioning
confidence: 99%
“…Similar studies have revealed that in rheological tests of hydrocolloidal and suspended foods, such food samples can be preferred to slide using smooth geometry (Buscall, 2010). In the rheological analysis of various food suspensions and dispersions such as chickpea puree (tomato puree, quince puree, ketchup, chickpea flour paste) to prevent wall slipping; pre-treatments such as using geometries with rough surfaces (Valencia et al, 2003), homogenizing particle size, using guar gum, xanthan gum and emulsifier additives (Bildir et al, 2018) were applied. After interpreting the shear rate versus shear stress graph by drawing, oscillation tests were also performed on chickpea purees prepared with the same dry matter content using dried chickpea puree powders, and the viscoelastic properties of the purees were determined.…”
Section: Rheological Propertiesmentioning
confidence: 99%